2012
DOI: 10.1088/0268-1242/27/10/105022
|View full text |Cite
|
Sign up to set email alerts
|

Height-driven linear polarization of the surface emission from quantum dashes

Abstract: The influence of the nanostructure height on the polarization of the surface emission was systematically investigated for In(Ga)As/InP quantum dashes. Polarization-resolved photoluminescence experiment was compared to theoretical considerations based on the multiband k•p theory and an analytical formula relating the polarization anisotropy to the nano-object geometry was derived. Substantial in-plane structure shape asymmetry induces a pronounced degree of linear polarization in surface emission, which depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…But on the other hand, the QDashes are similar to the investigated In 0.3 Ga 0.7 As/GaAs QDs with respect to the lack of in-plane rotational symmetry and the resulting lh contribution to the excitonic states. Much higher DOP-in the range of 0.15 up to 0.3-was observed experimentally [34,46]. This can be traced back to a larger lh contribution to the valence band ground state, in the range of 3.2-5.1% for QDash structures.…”
Section: A Degree Of Linear Polarization Of the Surface Emissionmentioning
confidence: 71%
“…But on the other hand, the QDashes are similar to the investigated In 0.3 Ga 0.7 As/GaAs QDs with respect to the lack of in-plane rotational symmetry and the resulting lh contribution to the excitonic states. Much higher DOP-in the range of 0.15 up to 0.3-was observed experimentally [34,46]. This can be traced back to a larger lh contribution to the valence band ground state, in the range of 3.2-5.1% for QDash structures.…”
Section: A Degree Of Linear Polarization Of the Surface Emissionmentioning
confidence: 71%
“…However, emission from the other edge (parallel to the Qdashes' longer lateral size) did not show any dependence of polarization on the dash height since the polarization was driven by the dashes longer lateral size rather than height [189]. A more detailed and systematic investigation of the Qdash height on the polarization of the surface emission was carried out by Musial et al [190] who showed through surface PL emission from these dashes was primarily driven by Qdash height due to heavy hole and light hole mixing.…”
Section: Qdashes On (100) Inp Substratementioning
confidence: 99%
“…In the first case, we attribute the 25% DOLP to the intrinsic property of the emitter which is driven by the heavy-hole light-hole mixing in the valence band that influences the optical transition dipole moments and the respective polarization components due to strong confinement anisotropy [23]- [25]. In case of QDashes it is evidently related to the elongation [26], but also depends on the nanostructure cross-sectional size [27].…”
Section: Resultsmentioning
confidence: 96%